EXPLORATORY RESEARCH OF THE IMPORTANCE OF INTEGRATED MARKETING COMMUNICATION OF WOLOAN WOODEN HOUSE - Tewu, Vanessa Violisari; Saerang, David P. E.; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Woloan Wooden house is one of the important assets on the economic sector in North Sulawesi, because this product is already known to spread out of Indonesia and it has an impact in economic progress especially in developing countries including Indonesia. Globalization is a challenge for the entrepreneurs of Woloan wooden house for maintaining their business. Using the Integrated Marketing Communication, especially for the promotion it provides an opportunity for the company of Woloan wooden house to improve the marketing power. The purpose of this study is to find out the importance of IMC of Woloan wooden house and what the elements of IMC used by the entrepreneurs for marketing development of Woloan wooden house. This research was conducted in Woloan as the marketing center of wooden house. Qualitative research is deployed and uses explosive research to the wooden house in Woloan and the sample took 13 entrepreneurs of Woloan wooden house. The results of this study explained that IMC is more effective tool and make it easier for the promotion of Woloan wooden house. In addition, through IMC the promotion of the products of Woloan wooden house can be better known by the people quickly.Keywords: integrated marketing communication